G632(P) How a tertiary children's hospital summer school influences attitudes to careers in paediatrics amongst medical student and foundation doctors. (May 2019) - Knott, C; King, J; Smith, J; Boyf, H; Poisson, J; Sharma, S; Winyard, P
Abstract : Aims: Recruitment to paediatric training has seen a 27.5% drop over the last three years, with significant effects on the trainee workforce. This has led to a growing number of initiatives to highlight the positives of the speciality and encourage applications including the successful #paedsrocks twitter campaign. There is a need to provide further sources of careers inspiration and guidance to potential applicants to allow them to explore careers in paediatrics further. Methods: We developed a 3 day Paediatric Summer School together with tertiary children's hospital clinicians, general paediatricians, paediatric researchers, academics and educators. The programme consisted of speciality experts describing their job and exciting innovations in their field, careers discussions, interactive QI and leadership group-work, and sessions delivered by former or current patients. To assess the impact this initiative had on perceptions of paediatrics and likelihood of application we sent a 9 question survey to attendees. Results: 55 medical students and foundation doctors attended the summer school. Medical students attended from 16 different UK medical schools, and 2 international medical students attended. 28/55 participants completed the survey. Attendees were asked to score their likelihood of a career in paediatrics on a 5-point Likert scale. The mean score before and after the summer school showed a statistically significant increase – 3.86 vs 4.68 (p=0.002). Most respondents felt the sessions about subspecialities and the careers talks made them feel more likely to apply for a career in paediatrics. 44% felt that long working hours were the biggest factor putting them off the speciality. Conclusion: There is a need to engage medical students and foundation doctors in order to foster positive attitudes towards paediatric careers and large tertiary children's hospitals and academic institutions are well placed to do this. The number of medical schools represented, suggests this is not being adequately provided locally. Our summer school shows this approach appears to have a positive impact on medical students and foundation doctors.